Analisis wacana kritis: perspektif tokoh wanita dalam film Pride and Prejudice terkait pernikahan - Burhamzah, Muftihaturrahmah; Alamsyah, Alamsyah; Asriati, Asriati (Jurnal Pendidikan Bahasa dan Sastra, 2021)
Critical discourse analysis of a film about marriage which is motivated by the concept of primogeniture becomes an interesting discourse to be studied. This study aims to analyze the concept of marriage from the point of view of the female character in the film Pride and Prejudice (2005) by using the critical discourse analysis method according to Norman Fairclough. This research is an explanatory research with a qualitative approach. The analysis was carried out through three stages, namely microstructural, mesostructural, and macrostructural analysis. From the research it was found that the perspective of each female character regarding marriage in the film Pride and Prejudice (2005) is influenced by two main things, namely the character's personal character and the character's living conditions according to the storyline. Jane Austen has the power to convey her ideology regarding primogeniture issues that occurred in society in her time to convey to readers through her novel Pride and Prejudice which director Joe Wright turned it into a film in 2005. Based on the results of the study, it can be concluded that marriage is influenced by Personal characters and living conditions in such a way shape the views and/or motives for the marriage of the female character in the film Pride and Prejudice (2005). Primogeniture is a factor of living conditions that most influence the perception of marriage in female characters in the film Pride and Prejudice (2005). The main problem in this storyline is related to the marriage of female characters, namely pride and prejudice.